Seafood HACCP Regulation: Basic Information for the Florida Seafood Industry - Razieh Farzad (EDIS)
This new 3-page document is the first in a "Seafood Guide" series, which seeks to help the seafood industry in Florida understand seafood safety regulations. Written by Razieh Farzad and published by the UF/IFAS Food Science and Human Nutrition Department. https://edis.ifas.ufl.edu/fs436